Reminiscing the legendary P. Ramlee through data visualization technique / Jawaheer Jaffar ... [et al.] - Jawaheer, Jaffar; Nur Afiqah, Ahmad Norazizi; Nasiroh, Omar; Sharifah, Aliman; Suraya, Masrom (UiTM Press, 2020)
P. Ramlee is a nickname for Tan Sri Datuk Amar Teuku Zakaria bin Teuku Nyak Putih. He is an evergreen and legendary Malaysian film actor, director, singer, songwriter, composer, and producer. Although the films related to him are mostly black and white, they are still the favourite characters of today's youth. To this day, the jokes and the pieces of advice contained in his work are still relevant in the current society. Due to his great contribution to the film industry and music literature, he is regarded as a famous icon of Malaysia entertainment. Acknowledging his contributions, many research works have been conducted and reported in academic journals but most of these works concentrated on the literary perspective of his artefacts. On the contrary, this paper provides additional knowledge on interactive and dynamic visualization techniques of the P.Ramlee unstructured data. The output of the work presented in this paper provides a fundamental knowledge on the design and implementation for effective visual data analytics.